Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

Overexpression of squalene synthase in withania somnifera leads to enhanced withanolide biosynthesis - Patel, Neha; Patel, Parth; Kendurkar, Shuchishweta V.; Thulasiram, Hirekodathakallu V.; Khan, Bashir Mohammad (Plant Cell Tissue and Organ Culture, 2015)
Genetic engineering of secondary metabolic pathways is an emerging area of research for production and improvement of natural products in plant biotechnology. Here, we describe a systematic approach to manipulate a key regulatory step of isoprenoid biosynthetic pathway in Withania somnifera to study its effect on withanolide production. We generated T-0 W. somnifera plants overexpressing squalene synthase (WsSQS) by Agrobacterium tumefaciens mediated transformation, which were analyzed by Gus biochemical assay and PCR of hygromycin phosphotransferase (hptII) and WsSQS. qRT-PCR analyses of various transformed tissues indicated 2-5 fold increase in WsSQS transcripts in both T-0 and T-1 generations. The tissue specific protein expression studies revealed 2-3 fold increase in WsSQS, which was further confirmed by enzyme activity. These observations were corroborated with the 1.5-2 fold increase in total withanolide content of the transformed tissues. However, in leaf tissue, the levels of Withaferin A and Withanolide A increased significantly up to 4-4.5 fold. These findings demonstrate genetic engineering of isoprenoid pathway in W. somnifera resulting in enhanced production of withanolides, and also provide insights into such metabolic pathways for their manipulation to improve the pharmacological content of different medicinally important plants.
Keywords: Agrobacterium tumefaciens; Solanaceae; Squalene synthase; Withania somnifera; Withanolides